PENINGKATAN HASIL BELAJAR PAI DENGAN METODE TEAM QIUZSISWA KELAS VI - Ernawati Ernawati (Jurnal Visi Ilmu Pendidikan, 2018)
The purpose of the research is to improve students achievement using Team Quiz method on the sixth grade of 07elementary school in East Pontianak, Pontianak City (Borneo). This research was Classroom Action Research, using John Elliotl model. The subjects were  sixth grade students. The data were collected  through  achievement  test,  observation  sheets,  questionnaires,  and  documentation.  The  data  were analyzed using descriptive quantitative and qualitative analysis.The results show that the implementation of Team Quiz method can improve the process and the results of religion studies on the sixth  grade. The improvement of learning process shown by students that are more active and communicative. In addition, the results indicated by the percentage of completeness in pre-action amounted to 41,93%, 61,29%  in the first cycle, and 90,32% in the second cycle.